1985
DOI: 10.1161/01.atv.5.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous and diet-induced coronary atherosclerosis in normal swine and swine with von Willebrand disease.

Abstract: We have observed that pigs with Impaired platelet function in the form of severe von Wlllebrand's disease (vWd) are resistant to spontaneous and to diet-Induced aortic atherosclerosis. However, it has been reported that vWd pigs are susceptible to coronary atherosclerosis produced by balloon-Induced injury of coronary arteries combined with an atherogenlc diet. We have evaluated the development of coronary atherosclerosis in normal control (NC) and homozygous vWd pigs In two prospective studies: 1) as a sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…6,24 These findings are supported by the results of a recently published study in mice with a complete deficiency of vWF. 9 Because vWF plays a role in primary and secondary hemostasis, protection against atherosclerosis could be explained by decreased adhesion and aggregation of platelets to endothelial and subendothelial structures [25][26][27] and by decreased plasmatic coagulability.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…6,24 These findings are supported by the results of a recently published study in mice with a complete deficiency of vWF. 9 Because vWF plays a role in primary and secondary hemostasis, protection against atherosclerosis could be explained by decreased adhesion and aggregation of platelets to endothelial and subendothelial structures [25][26][27] and by decreased plasmatic coagulability.…”
Section: Discussionsupporting
confidence: 69%
“…In the pigs, protection against aortic atherosclerosis was found, whereas no protection was found in the coronary arteries. 8,24,31,32 It is known that the pace of development of atherosclerosis is different for the various sites in the vessel tree, depending on some recognized factors, such as shear stress, and some as yet unknown factors. 33 In the present study, we found advanced atherosclerotic lesions and found no differences between groups.…”
Section: Discussionmentioning
confidence: 99%
“…The first experimental data suggested that the absence of vWf provided an atheroprotective effect in pigs. 23,24 However, it was later shown that the atherogenic diet leads to a variable degree of hypercholesterolemia caused by a polymorphism in apolipoprotein B100, 10,25 making it difficult to draw a definitive conclusion about the involvement of vWf in atherosclerosis. In contrast, mice deficient in vWf represented a model with a defined genetic background and allowed us to show in the present study that the absence of vWf significantly delays the formation of atherosclerotic lesions in mice on the LDLR-deficient background.…”
Section: Discussionmentioning
confidence: 99%
“…6 7 8 Also intriguing is the possible relationship between our finding of no detectable vWF in normal swine coronary arteries and the finding of a low frequency of spontaneous coronary atherosclerosis in normal, as well as von Willebrand disease, pigs. 22 Further studies will be necessary to explore the potential relationship between vWF in this site and its proclivity toward atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%